Ramsay Hunt Syndrome. A Case Report - Nicolau Chafick Miguel Júnior; Joseph Bruno Bidin Brooks (Journal of Clinical Case Reports and Images, 2020)
This case report describes facial nerve palsy due to Ramsay Hunt syndrome, highlighting otic vesicles, audiovestibular symptoms, and imaging considerations. Management with antivirals, corticosteroids, and supportive care is summarized. Early recognition can improve outcomes and limit sequelae.
Keywords: Ramsay Hunt Syndrome